Estriol in pregnancy and x-linked recessive ichthyosis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2014)
The differential diagnosis between X-linked ichthyosis (Fig. 1) and congenital lamellar ichthyosis (Fig. 2) is easy when the history highlights only affected males in the maternal family. In our case it is less easy, and must be confirmed by the presence of other data such as corneal opacities in slit lamp examination – in our case absent, as occurring in 50% of cases –, demonstration of increased migration rate (2 mm more of controls) of low-density lipoprotein fraction on electrophoresis of serum lipoproteins – test rarely available and subject to misinterpretation –, dosage of steroid sulfatase in leukocytes and fibroblasts – test available in a few laboratories nationwide –. In case of doubt it is therefore possible to ask the mother if she performed during pregnancy the triple test, increasingly used today to rule out chromosomal abnormalities: low levels of free estriol will confirm the diagnosis of X-linked ichthyosis.